2021
DOI: 10.5435/jaaos-d-20-01022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Operating Room Size on Orthopaedic Surgical Site Infection Rates

Abstract: Objective: With many preventable causes of surgical site infections (SSIs) identified, the effect of operating room (OR) size on SSI rates has not been assessed. This study investigated the effect of OR size on incidence of SSIs for orthopaedic procedures. Background: SSIs remain a common complication within the perioperative realm. Responsible for increasing length of hospitalization and costs, SSIs result in a decreased quality of life for patients. Methods: A retrospective review of 11,163 patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…An overall infection rate of 1.57% (111 of 7,052 patients) was observed, consistent with previous reports in the literature 17,18 . Holes in the wrap and/or filter of the instrument tray were the most common reason for IUSS use, followed by instrument reuse and dropping (see Appendix Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…An overall infection rate of 1.57% (111 of 7,052 patients) was observed, consistent with previous reports in the literature 17,18 . Holes in the wrap and/or filter of the instrument tray were the most common reason for IUSS use, followed by instrument reuse and dropping (see Appendix Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Recent research has shown that various factors, such as prolonged operating room time, the size of the operating room, frequent door openings, suboptimal layout of operating rooms, and the behavior and number of personnel, contribute to increased contamination levels in the operating environment. 36-39 It is important to note that while control blades in this study have shown positive results for contamination, this does not necessarily imply a heightened risk of surgical site infection. Instead, these findings may underscore the sensitivity of NGS to detect minute quantities of bacterial DNA.…”
Section: Discussionmentioning
confidence: 74%
“…Here we present findings of a single OR which may help mitigate size of the OR as a potential study confounder. This may increase the strength of this study as size of the operating room has been shown in previous work to affect SSI rates [23]. The use of laminar ventilation was utilized in the observed OR, which has been shown in previous work to reduce OR bacterial counts when compared to turbulent airflow, though the effect on SSI still unclear [6,8].…”
Section: Discussionmentioning
confidence: 94%